Integrating short- and full-length 16S rRNA gene sequencing to elucidate microbiome profiles in Pacific white shrimp ( Litopenaeus vannamei ) ponds - Rajonhson, Dora M.; Angthong, Pacharaporn; Thepsuwan, Timpika; Sutheeworapong, Sawannee; Satanwat, Penpicha; Tapaneeyaworawong, Paveena; Powtongsook, Sorawit; Kruasuwan, Worarat; Jenjaroenpun, Piroon; Wongsurawat, Thidathip; Chaiyapechara, Sage; Rungrassamee, Wanilada (Microbiology spectrum, 2024)
This interdisciplinary study investigated the influence of sequencing techniques on bacterial communities profiling within Pacific white shrimp ( Litopenaeus vannamei ) ponds. By integrating aquaculture, microbiology, and environmental science, we revealed the role of ecological niches and factors like salinity and pH on microbiota diversity and composition in shrimp intestines, pond water, and sediment. Additionally, we compared the taxonomic resolution using partial versus full-length 16S rRNA gene sequences, highlighting the value of longer amplicons for precise identification of key taxa. These findings provide novel insights into microbial dynamics underlying environmental effects in shrimp aquaculture. Comprehensive characterization of the pond microbiome could lead to management strategies that promote shrimp health and productivity. Furthermore, the potential of a multi-omics approach for integrating complementary data streams to elucidate environment-microbiome-host interactions was highlighted.